Energy production from piggery waste using anaerobic digestion: Current status and potential in Cyprus - Theofanous, Elisavet; Kythreotou, Nicoletta; Panayiotou, Gregoris; Florides, Georgios A.; Vyrides, Ioannis (My University, 2014)
In this work the current status and the potential of biogas production and energy generation through the anaerobic digestion of piggery waste in Cyprus are presented. The onsite use of anaerobic digestion for treating piggery waste not only generates renewable energy, but it is also a sustainable waste management solution. The actual values of the biogas production (20,475m3/day) and the energy generation are compared with the theoretical values, which are in line with several units. The value 20m3/tonne of pig waste was found to predict more accurately the biogas, heat and electricity production compared to the value of 36m3/tonne of pig waste. Moreover, an empirical equation (R2=0.9939) is proposed for calculating the biogas production per day, according to the volume of pig waste treated per day BGP=14.64 (PWT)+535. The potential biogas production from the total pig population of Cyprus equals to 29,734,356m3/yr and the potential thermal and electrical energy are calculated to be 90.85GWhth/yr and 63.59GWhel/yr, respectively. Finally future alternatives on anaerobic digestion in Cyprus are presented such as co-digestion, centralized anaerobic digestion, hydrothermal pre-treatment, possible use of fuel cells and efficient utilization of pig slurry.
Keywords: Anaerobic digestion; Biogas production; Cyprus; Energy generation; Piggery waste